Discovery of novel gating checkpoints in the Orai1 calcium channel by systematic analysis of constitutively active mutants of its paralogs and orthologs. (July 2022) - Augustynek, Bartłomiej; Gyimesi, Gergely; Dernič, Jan; Sallinger, Matthias; Albano, Giuseppe; Klesse, Gabriel J.; Kandasamy, Palanivel; Grabmayr, Herwig; Frischauf, Irene; Fuster, Daniel G.; Peinelt, Christine; Hediger, Matthias A.; et al.
Highlights: The TM2-TM1 coupling is conserved in all human Orai channel paralogs, whereas the TM4-TM3 coupling appears to be altered. Contrary to Orai1, introduction of the ANSGA substitution does not activate Orai2 and Orai3 channels. The Xenopus Orai1-ANSGA mutant is constitutively active, whereas the Drosophila Orai-ANSGA is not. Orai1 residues H171 and F246 are critical for its activation by the ANSGA substitution, but not by STIM1. The ANSGA mutant itself may not be an accurate surrogate for the STIM1-activated Orai1 channel. Abstract: In humans, there are three paralogs of the Orai Ca 2+ channel that form the core of the store-operated calcium entry (SOCE) machinery. While the STIM-mediated gating mechanism of Orai channels is still under active investigation, several artificial and natural variants are known to cause constitutive activity of the human Orai1 channel. Surprisingly, little is known about the conservation of the gating checkpoints among the different human Orai paralogs and orthologs in other species. In our work, we show that the mutation corresponding to the activating mutation H134A in transmembrane helix 2 (TM2) of human Orai1 also activates Orai2 and Orai3, likely via a similar mechanism. However, this cross-paralog conservation does not apply to the "ANSGA" nexus mutations in TM4 of human Orai1, which is reported to mimic the STIM1-activated state of the channel. In investigating the mechanistic background of these differences, we identified two positions, H171 and F246 in human Orai1, that are not conserved among paralogs and that seem to be crucial for the channel activation triggered by the "ANSGA" mutations in Orai1. However, mutations of the same residues still allow gating of Orai1 by STIM1, suggesting that the ANSGA mutant of Orai1 may not be a surrogate for the STIM1-activated state of the Orai1 channel. Our results shed new light on these important gating checkpoints and show that the gating mechanism of Orai channels is affected by multiple factors that are not necessarily conserved among orai homologs, such as the TM4-TM3 coupling. Graphical abstract: Image, graphical abstract